Above the salt - Vaz, Katherine (Flatiron Books, 2023)
"John Alves, son of a famous Presbyterian martyr on the Portuguese island of Madeira, spends his childhood in jail and in poverty. When he meets Mary Freitas--though the adopted daughter of a master botanist, her true lineage is the subject of dangerous rumor--a spark kindles a lasting bond. But soon their families must confront the rising blood tide of warfare between Catholics and Protestants. Fleeing with only what they can carry, John and Mary are separated and arrive at different times and places in a rapidly growing and changing mid-nineteenth-century Illinois. Years later, John settles into his life as an educator at Jacksonville's nationally renowned school for the deaf, and Mary is a gardener in Springfield for handsome, wealthy Edward Moore. After John and Mary reconnect, the home of rising politician Abraham Lincoln provides a prime setting for their courtship. But conflict looms on the horizon, and John is torn. Should he join the Union army to prove his loyalty to his new country, or should he stay to fight for the chance to make a life with the one he loves? And should Mary accept Edward's marriage proposal since he is a partner in her business of selling the miracle-berry fruit she transported from Madeira, or should she choose her passion for John? Social jealousies and betrayals compound the obstacles unleashed by the Civil War. In poignant and lyrical prose, Katherine Vaz's Above the Salt is a captivating and beautiful tribute to the power of true love and the sacrifices we make to harness it"--